Selective C−O Hydrogenolysis of Erythritol over Supported Rh‐ReOx Catalysts in the Aqueous Phase. Issue 14 (16th May 2017) - Said, Achraf; Da Silva Perez, Denilson; Perret, Noémie; Pinel, Catherine; Besson, Michèle
Abstract: Bimetallic Rh‐ReO x (Re/Rh molar ratio 0.4–0.5) catalysts supported on TiO2 and ZrO2 were prepared by the successive impregnation of dried and calcined unreduced supported Rh catalysts. Their catalytic performances were evaluated in the hydrogenolysis of erythritol to butanetriols (BTO) and butanediols (BDO) in aqueous solution at 150–240 °C under 30–120 bar H2 . The activity depended on the nature of the support, and the highest selectivity to BTO and BDO at 80 % conversion was 37 and 29 %, respectively, in the presence of 3.7 wt %Rh‐3.5 wt %ReO x /ZrO2 at 200 °C under 120 bar. The characterization of the catalysts by CO chemisorption, TEM with energy‐dispersive X‐ray spectroscopy, thermogravimetric analysis with MS, and X‐ray photoelectron spectroscopy suggests a different distribution and reducibility of Re species over the supported Rh nanoparticles, which depends on the support. Abstract : Scissors for C−O bonds : Selective C−O hydrogenolysis is a challenging strategy to remove the hydroxyl groups of oxygenated biomass‐derived molecules. Reaction pathways for erythritol in water are studied over TiO2 ‐ and ZrO2 ‐supported Rh‐ReO x catalysts. With the use of ZrO2 as a support, a selectivity up to 66 % butanetriols and butanediols is achieved at 80 % conversion.